Maternal serum atrial natriuretic peptide (ANP) and brain-type natriuretic peptide (BNP) levels in gestational diabetes mellitus. (2nd August 2016) - Yuksel, Mehmet Aytac; Alici Davutoglu, Ebru; Temel Yuksel, Ilkbal; Kucur, Mine; Ekmekci, Hakan; Balci Ekmekci, Ozlem; Uludag, Sezin; Uludag, Seyfettin; Madazli, Riza
Abstract: Objective : The aim of the study is to evaluate maternal serum atrial natriuretic peptide (ANP) and brain-type natriuretic peptide (BNP) levels in patients with getational diabetes mellitus compared with a control group. Methods : We have measured maternal serum ANP and BNP levels in 35 otherwise healthy and 45 gestational diabetic women between gestational week 24 and 28 referred to our unit in a cross-sectional study. Independent samples t -test or the Mann–Whitney U -test was used for comparison of two groups where appropriate. Results : Mean maternal serum homeostasis model assessment of insulin resistance (HOMA-IR), HbA1c, fasting glucose and insulin levels in gestational diabetes mellitus (GDM) group were significantly higher than the control group ( p < 0.01). Mean maternal serum ANP and BNP levels of women with GDM were significantly lower than the control group (12.9 ± 9.9 versus 34.8 ± 16.9 pg/ml, p < 0.001; 416.6 ± 209.7 versus 629.7 ± 162.2 mg/dl, p < 0.001, respectively). Maternal serum ANP and BNP levels were negatively correlated with insulin levels, HbA1c and HOMA-IR values ( p < 0.05). Conclusions : Maternal serum ANP and BNP levels are significantly lower in patients with GDM. These biomarkers might be valuable in clinical setting for identifying high-risk women for developing diabetes during pregnancy.